Carbohydrate/glycan-binding specificity of legume lectins in respect to their proposed biological functions - Ramos,Márcio Viana (2000)
The lectins, proteins which specifically recognize carbohydrate moieties, have been extensively studied in many biochemical and structural aspects in order to establish the molecular basis of this non-catalytic event. On the other hand, their clinical and agricultural potentials have been growing fast. Although lectins, mainly those from legume plants, had been investigated for biological properties, studies about the physiological functions of lectins are scarce in literature. Therefore, despite the accumulated data on lectins (as proteins), the role played by these signalizing molecules is poorly discussed. In the light of our accumulated results on legume lectins, specially those obtained from plants belonging to the Diocleinae sub-tribe and available data in literature, we discuss here the main hypothesis of their functions according to their carbohydrate/glycan-binding specificity.